2019
DOI: 10.15171/jlms.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Effect of Different Surface Treatments of a Hybrid Ceramic on the Microtensile Bond Strength to a Luting Resin Cement

Abstract: Please cite this article as follows: Motevasselian F, Amiri Z, Chiniforush N, Mirzaei M, Thompson V. In vitro evaluation of the effect of different surface treatments of a hybrid ceramic on the microtensile bond strength to a luting resin cement. Abstract Introduction:The aim of the present study was to investigate the effect of different surface treatments of a hybrid ceramic, Vita Enamic, on the micro-tensile bond strength (µ-TBS) to resin cement. Methods: Ten blocks (3×10×8 mm) were retrieved from the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Numerous studies have attempted to find an optimal sandblasting protocol by varying the pressure or duration of treatment. The optimal treatment would be sandblasting between 1 and 3 bar for 5 to 60 s, depending on the study and the type of composite [ 32 , 33 ]. However, it has been shown that sandblasting may damage the surface of composite CAM-CAM blocks if the procedures (pressure, duration, type of abrasive particle) are not optimized [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to find an optimal sandblasting protocol by varying the pressure or duration of treatment. The optimal treatment would be sandblasting between 1 and 3 bar for 5 to 60 s, depending on the study and the type of composite [ 32 , 33 ]. However, it has been shown that sandblasting may damage the surface of composite CAM-CAM blocks if the procedures (pressure, duration, type of abrasive particle) are not optimized [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…HF acid application resulted in the highest bond strength values. 19 Motevasselian et al 6 tested the effectiveness of Er: YAG laser, HF acid, Al 2 O 3 sandblasting, and phosphoric acid applications. The highest bond strength values between VE-resin cement were observed in the HF acid group, while the lowest bond strength values were observed in the Er: YAG laser group.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on the subject have conflicting findings. [5][6][7] Manso and Carvalho 8 found that since resin-matrix ceramics are the latest to be introduced to the dental market, limited studies have been performed for the optimal clinical protocol regarding the surface treatments for ideal bonding and the results were also material-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the liability of low energy power output to result in a less defined penetration zone of the resin cement, where the outermost layer of the ceramic remains interlocked with the resin cement; leaving the underlying ceramic intact and thus causing less energy transmission. 18,21 Type III cohesive failure within the cement in all of the debonded specimens could be attributed to the ability of laser to soften the outer surface of the resin cement and targeting the water content of the cement, causing micro explosions within the water content of the cement. These finding corelates with Karagoz et al who stated that cohesive failure was found within the cement layer as the debonding laser procedure degrades the resin cement without damaging either the tooth structure or the veneer.…”
Section: Discussionmentioning
confidence: 99%